ANALISIS PENERAPAN KREDIT USAHA MIKRO KECIL MENENGAH PADA PT. BPR EKA BUMI ARTHA CABANG UNIT II TULANG BAWANG - Rudy - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
Credit evaluation is an important element in the provision of credit to debtors. Lendingactivities, we need a good and thorough analysis of all aspects of credit that can support the loanprocess, in order to prevent the occurrence of a credit risk.The purpose of this study is to investigate the application of credit made by the PT BPR EkaBumi Artha. From the analysis of data using analysis tools 5C is a character, capacity, capital,collateral and condition can determine debtors whether or not receive a credit of PT BPR Eka BumiArtha.